(untitled) (Journal of Parents and Teachers, 2025)
Joaquín M.ª García de Dios addresses the issue of family mediation, which helps families going through separation or divorce to resolve conflicts as fairly and peacefully as possible. Family mediation protects children and encourages responsible agreements between both parents.